2016
DOI: 10.4236/jwarp.2016.89067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Advanced Oxidation Processes on the Decomposition Properties of Organic Compounds with Different Molecular Structures in Water

Abstract: Studies to decompose persistent organic pollutants in wastewater from chemical factories by using Advanced Oxidation Processes (AOPs) have recently been performed. Oxidation reactions involving ozone and •OH radicals and cleavage caused by UV are the main decomposition reactions that occur in AOPs using ozone and UV. The mechanisms through which organic compounds are decomposed in AOPs are complicated and difficult to understand because various decomposition reactions occur simultaneously. The Total Organic Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Differences in the removal rates of the examined compounds, which were observed in all conducted AOPs, results mainly from the different chemical structures of the decomposed compounds. Suzuki et al [28] reported that aromatic compounds were slower to degrade than the open-chain compounds. Additionally, the number of carbon atoms and the presence of functional groups determine the ability of a compound to decompose [28].…”
Section: Degradation Of Micropollutants In Uv-based Aopmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the removal rates of the examined compounds, which were observed in all conducted AOPs, results mainly from the different chemical structures of the decomposed compounds. Suzuki et al [28] reported that aromatic compounds were slower to degrade than the open-chain compounds. Additionally, the number of carbon atoms and the presence of functional groups determine the ability of a compound to decompose [28].…”
Section: Degradation Of Micropollutants In Uv-based Aopmentioning
confidence: 99%
“…Suzuki et al [28] reported that aromatic compounds were slower to degrade than the open-chain compounds. Additionally, the number of carbon atoms and the presence of functional groups determine the ability of a compound to decompose [28]. The type of chemical bonds between the atoms of the compound molecule and their energy also determines the emerging decomposition by-products and their future mineralization.…”
Section: Degradation Of Micropollutants In Uv-based Aopmentioning
confidence: 99%
“…The second category is unreacted polycyclic naphthenic acids which are NAs that contain at least one cyclical structure and did not undergo oxidation in the previous process (Figure 8). Figure 2.12 Oxidation of an Aldehyde into a Carboxylic Acid (Suzuki, et al, 2016) The method for biodegradation of these products will be through heterotrophic metabolism using blue green algae, Spirulina platensis. Blue green algae are photosynthetic unicellular prokaryotic organisms that live in diverse aquatic habitats ranging from cold salt water to tropical freshwater bodies (Vonshak, 2014).…”
Section: Figure 27 Saturated Fatty Acidsmentioning
confidence: 99%
“…1 Summary of Technological advances in the Produced Water treatment and Potential Applications to The Oil Sand Industry (Allen 20018) (Cabrera, 2008) (Eriksson, 2005;Gehringer et al, 1999) (Suzuki, et al, 2016) ................. Figure 2.13 Fatty Acid Biosynthesis process for Cyanobacteria.…”
mentioning
confidence: 99%
“…Thus, developing new methodologies and materials to treat wastewater is essential. Up to this point, treatments such as adsorption, 2,3 advanced oxidation processes (AOPs), 4,5 and wet oxidation 5 have been used. Moradi et al 6 performed batch adsorption experiments to study zeolite, nano zero-valent iron (nZVI)-zeolite, nZVI, and iron powder adsorbents on nitrate removal performance and researched their feasibility and strong pH dependence upon nitrate adsorption to adsorbents.…”
Section: Introductionmentioning
confidence: 99%